The Architectural Uncanny: An Essay in the Postcolonial Unhomely. Issue 1 (2nd January 2016) - Obert, Julia C.
Abstract : This essay argues that (post)colonial cities are often studies in what Anthony Vidler calls the 'architectural uncanny'. Imperial powers use mapping, building and urban design projects literally to shift the ground beneath natives' feet – a strategy that makes familiar ground seem uncannily foreign. The essay takes Belfast as a case study, tracing significant elements of the British design programme in the city from the seventeenth century onwards and connecting these elements to the segregated, sectarianized geography of the contemporary (post-)conflict city. However, far from ascribing absolute power to this 'unhomely' landscape, this essay examines the ways in which architectural space enables structures of both subjection and subversion. It reads the work of writers Ciaran Carson and Glenn Patterson for insubordinate spatial practices, practices that refute architectural authority by salvaging unpredictability, even play, for local pedestrians. These subterranean navigational tactics allow natives to re-route and re-root, at least in part, in their uncanny city.